Role Stress and Turnover Intention of Front-Line Hotel Employees: The Roles of Burnout and Service Climate - Wen, Biyan; Zhou, Xiaoman; Hu, Yaou; Zhang, Xiao (Frontiers in Psychology, 2020)
High turnover rate represents one of the most significant challenges the hotel industry faces. High turnover rates mean labor shortages, resulting in high costs of recruiting, staffing and training. Turnover also has a negative impact on service quality. Scholars continue to search for the root causes of turnover and propose solutions. To further understand employees’ turnover intention, this study reveals the role of stress on hotel front-line employees’ turnover intention through the mediation of burnout. Moreover, the study examines the moderating effect of service climate on the underlying mechanism that links role stress with turnover intention. Using a sample of 583 questionnaires from front-line hotel employees in South China, this study reveals that role stress as a four-dimensional construct (i.e., conflict, ambiguity, qualitative overload and quantitative overload) has a statistically significant impact on burnout, which leads to turnover intention. Burnout completely mediates the relationship between role stress and turnover intention, that is, employees under role stress do not resign immediately unless they experience high levels of burnout. In addition, service climate moderates the influence of role stress on burnout, suggesting a moderated mediation relationship. The study contributes to the organizational management literature by confirming the four dimensions of role stress and demonstrating how role stress impacts employees’ turnover intention. Furthermore, the critical effect of service climate is further investigated. Theoretical contributions and managerial implications are discussed based on the findings. the study also investigates the moderating effect of service climate on role stress (challenge-hindrance stressors) and burnout.